Pengaruh Perilaku Kepemimpinan Berorintasi Hubungan Dan Disiplin Kerja Terhadap Efektivitas Perubahan Organisasi pada PT. Paya Pinang Medan - Genias Idealman Laia (JOURNAL ECONOMICS AND STRATEGY, 2024)
This research aims to determine the influence of Relationship-Oriented Leadership Behavior and Work Discipline on the Effectiveness of Organizational Change at PT. Paya Pinang Medan, knowing the influence of Relationship-Oriented Leadership on the Effectiveness of Organizational Change of PT employees. Paya Pinang Medan and knowing the influence of Relationship-Oriented Leadership Behavior and Work Discipline simultaneously on the Effectiveness of Organizational Change at PT. Paya Pinang Medan. This research is aquantitative descriptive research with a questionnaire instrument with a population of all PT employees. Paya Pinang Medan as many as 78 people. By drawing samples using total sampling or saturated samples, a sample of 78 people was obtained. Relationship-oriented leadership has a significant effect on the effectiveness of organizational change and is the dominant variable influencing the effectiveness of organizational change at PT Paya Pinang Medan, with a sig value <0.05.